Microleakage of different temporary luting agents used for cementing provisional restorations on custom cast posts and cores - Maryam Mohajerfar; Naeemeh Nikfarjam Nouri; Tabasom Hooshmand; Elaheh Beyabanaki (Wolters Kluwer Medknow Publications, 2021)
Background: This study aimed to compare the effect of four temporary luting agents on preventing the coronal microleakage of teeth restored with custom cast post and core. Materials and Methods: In this in vitro original study, after removing 9 mm of gutta percha from root canals of 32 single-canaled premolars, the acrylic resin patterns of the post and core were fabricated. Patterns were cast with Ni-Cr metal alloy and then cemented with glass ionomer. Using self-curing acrylic resin, provisional restorations were made. Then, teeth were randomly allocated to four groups for each temporary cement including zinc oxide eugenol (Temp Bond), zinc oxide noneugenol (Temp Bond NE), noneugenol resin-based temporary luting agent (Temp Bond Clear), and noneugenol urethane methacrylate polymer-based temporary luting agent (Dento temp). Teeth were subjected to thermocycling, immersed in silver nitrate for 6 h and then sectioned. The amount of dye penetration in the margin of provisional crown and into the coronal part of the root canals was measured using a stereomicroscope. Data were analyzed using the Kruskal-Wallis and Dunn tests with significance level of 0.05. Results: All the luting agents showed some degree of microleakage (Group 1 showed the most microleakage). According to the pair comparison between the groups, Group 1 revealed a significant difference with others (P < 0.05). Furthermore, Group 2 showed more microleakage as compared to Group 4 (P = 0.037). Conclusion: Temp Bond showed the highest microleakage as compared to other luting agents. Furthermore, Temp Bond NE revealed a weaker sealability as compared to Dento temp.